A proposed guidance program and in-service training for the Divine Word College high school department - Blaza, Rosita D. (Animo Repository, 1974)
This study aims to find out the needs of the students and the extent to which these needs are being met, to define ways and means to meet these needs better, to find out the needs of the faculty that necessitates an in-service training, and to plan out an in-service program that will best suit the needs of the faculty. A survey of the high school department of the Divine Word College of San Jose, Occidental Mindoro was conducted for the school year 1973-74. The subjects of the study included 258 first and second year high school students, 149 third and fourth year high school students, 40 parents, and 14 high school teachers. The Mooney Problem Check List, Junior Form, was administered to the first and second year high school students. The high school form of the Mooney Problem Check List was administered to the third and fourth year high school students. A questionnaire-opinionnaire was given to the randomly selected parents, together with a letter explaining its purpose. To secure the teachers' reactions to their own guidance practices, a questionnaire adapted from Roeber, Smith, and Erickson (1955) was used. The result of the survey questions attached to the Mooney Problem Check List, junior and high school form, except that on the problem bothering them most, were combined. With these and with the result of the questionnaire given to the parents, tallying and ranking the frequencies, summing the frequencies and solving for the percentage were mostly used. Based on the findings of the study, it was concluded that the needs of the first and second year students were on the areas of money, work, future, school, self-centered concern, health, and physical development. The problems of the third and fourth year students were on finances, living conditions, employment, adjustment to school work, and the future: vocational and educational. The needs of the high school students were being met through incidental guidance services. Also, the needs of the high school students can be better met through an organized guidance program. The needs that necessitate an in-service training for the faculty were : a) better acquaintance with students, b) improvement on the use of guidance resources, c) organized services to students, d) prevention of difficulties from happening, and e) reorganization of subject to provide special services to the students. It was also concluded that a developmental in-service training will best suit the needs of the faculty.